PENGARUH TERAPI DZIKIR TERHADAP KECEMASAN IBU HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS PAYUNG SEKAKI - Hotmauli Hotmauli; Sulastri Delvi Yanti (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Anxiety is a common psychological disorder among pregnant women, particularly during the third trimester approaching labor. If left unmanaged, anxiety may negatively affect the physical and psychological health of the mother, as well as fetal development. One non-pharmacological method to alleviate anxiety is dzikir therapy, which involves the repetition of religious phrases that can promote relaxation, calmness, and spiritual closeness to Allah SWT. Objective:This study aimed to examine the effect of dzikir therapy on anxiety levels in third trimester pregnant women in the working area of Payung Sekaki Public Health Center, Pekanbaru. Method: This research used a quantitative method with a quasi-experimental design (one group pretest-posttest). The sample consisted of 34 third trimester pregnant women experiencing anxiety, selected using total sampling based on inclusion criteria. Anxiety levels were measured using the Hamilton Rating Scale for Anxiety (HRS-A) before and after the intervention. The dzikir therapy was administered twice daily (morning and evening) for two weeks. Data were analyzed using univariate and bivariate analysis, with a paired sample t-test for significance testing.Results: The results showed that before the intervention, most participants experienced moderate anxiety (70.6%), while after the intervention, most experienced mild anxiety (85.3%). The average anxiety score decreased from 24.79 to 17.55. The statistical test showed a p-value of 0.000 (p 0.05), indicating that dzikir therapy had a significant effect on reducing anxiety levels. Conclusion: , dzikir therapy is effective as a non-pharmacological intervention for reducing anxiety in third trimester pregnant women. It is recommended as a spiritual-based method that is simple, cost-effective, and can be performed independently. Health workers are encouraged to educate pregnant women on the benefits of dzikir therapy as part of promotive and preventive maternal health services.Keywords: Dzikir Therapy, Anxiety, Pregnant Women, Third Trimester, HRS-A.